Should We Replace the Universal Health Coverage with the Co-Payment Scheme?: A Theory for a Small Open Economy like Thailand - Thaweesatidsatean, Pongsak; Thepmongkol, Athakrit (Journal of Applied Economics and Management Strategy [eISSN 2985-1408], 2022)
ABSTRACT This paper aims to theoretically analyze pros and cons between implementing the Universal Health Coverage (UHC) and the Co-Payment Scheme (CPS) in a small open economy with the focus on Thailand by using two-period Overlapping Generations Model (OLG). The result is that as long as the public debt level is still manageable, the UHC is recommended over the CPS to countries like Thailand where people have low intertemporal elasticity of substitution as it promotes good health, GDP, consumptions, savings, and even economic stability.